Short Message Service: Offline Notification System through Bulk SMS for Android Application - Kale, Harshad; Rane, Ganesh; Shende, Sagar; Shinde, Swapnil (International Journal of Computer Sciences and Engineering, 2014)
In this paper we have implement offline notification system through Bulk sms for android application. Short message service is a message technology (only for mobile) that enables the sending and receiving of messages between any mobile phones. Bulk Messaging is the dissemination of large numbers of SMS messages for delivery to any mobile phone terminals. It is used by media companies, enterprises, banks, colleges and consumer brands for a variety of purposes including entertainment, enterprise and mobile marketing. for also purpose of notification system. Bulk messaging is commonly used for alerts, reminders, marketing, and notification but also for information and communication between both staff and customers. Bulk messaging lets you deliver SMS messages to mobile handsets almost anywhere in the world.